Research on Semi-physical Simulation for the Main Drive System of High PowerAC-DC-AC Rolling Mill - TAN Juan; ZHANG Yu; CHEN Liusong (Kongzhi Yu Xinxi Jishu)
It analyzed a semi-physical simulation system for the main drive system of high-power AC-DC-AC rolling mill based on dSPACE. Virtual scene were constructed for the simulation system, debugging and test running environment were made through real-time simulator for the converter controller. It completely meets the requirements of various functions and performances in debugging and testing of the main drive system for high power AC-DC-AC rolling mill, and greatly reduces dependence of the controller for medium voltage drive converter on the test resources.